Partitioning variance in cortical morphometry into genetic, environmental, and subject-specific components - Smith, DM; Parekh, P; Kennedy, J; Loughnan, R; Frei, O; Nichols, TE; Andreassen, OA; Jernigan, TL; Dale, AM (Oxford University Press, 2024)
The relative contributions of genetic variation and experience in shaping the morphology of the adolescent brain are not fully understood. Using longitudinal data from 11,665 subjects in the ABCD Study® , we fit vertexwise variance components including family effects, genetic effects, and subject-level effects using a computationally efficient framework. Variance in cortical thickness and surface area is largely attributable to genetic influence, whereas sulcal depth is primarily explained by subject-level effects. Our results identify areas with heterogeneous distributions of heritability estimates that have not been seen in previous work using data from cortical regions. We discuss the biological importance of subject-specific variance and its implications for environmental influences on cortical development and maturation.